2020
DOI: 10.26717/bjstr.2020.26.004338
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Outcome in Gestational Diabetes Melitus Vs Normoglycemic Women

Abstract: Introduction: Gestational Diabetes Mellitus (GDM) is glucose intolerance diagnosed for the first time in pregnancy. It may lead to potentially serious short term and longterm complications for both mother and fetus or newborn. Material and Methods:Prospective study was conducted at the University clinic for gynecology and obstetrics, Skopje for the period of one year. 100 pregnant women in the second trimester which performed oral glucose tolerance test (75g OGTT) were evaluated. The study included 50 women wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
3
2
1
Order By: Relevance
“…While studies reported higher risks of preterm [ 49 ], macrosomia [ 8 ] and high birthweight [ 50 ] births in GDM, we did not observe these associations in SBC and GUSTO cohorts. This may be explained by effective dietary interventions as women in both cohorts attended prenatal care in high-quality tertiary care centers.…”
Section: Discussioncontrasting
confidence: 99%
“…While studies reported higher risks of preterm [ 49 ], macrosomia [ 8 ] and high birthweight [ 50 ] births in GDM, we did not observe these associations in SBC and GUSTO cohorts. This may be explained by effective dietary interventions as women in both cohorts attended prenatal care in high-quality tertiary care centers.…”
Section: Discussioncontrasting
confidence: 99%
“…Study in the USA demonstrated that 1.5–4% of newborns from mothers with GDM developed RDS [ 78 ]. Similarly, previous studies also shown that infants from women with GDM had higher risk of developing RDS [ 74 , 75 , 87 ]. This might be associated with the effects of hyperglycemia delays fetal lung maturity.…”
Section: Discussionsupporting
confidence: 59%
“…The pooled prevalence of preterm birth among mothers with HIP was 16.9%. Previous reports also demonstrated this higher risk of prematurity among women with GDM [ 75 , 78 , 83 , 87 ]. This high risk of prematurity might be associated with early induction of labor before 39 weeks of gestation and/or premature rupture of membranes [ 79 ].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…5 GDM presents immediate risks to maternal health including increased likelihood of pre-term labour and developing hypertensive disorders of pregnancy, and in the infant a higher risk such as being born large for gestational age and shoulder dystocia. [6][7][8] Long-term impacts include increased risk of developing type 2 diabetes mellitus (T2DM) in later life for the mother, and infants exposed to GDM in-utero are more likely to develop obesity. 9 10 Gestational weight gain (GWG) is essential to support pregnancy, the National Academy of Medicine (NAM) published guidelines for a maximum GWG per week, dependent on the women's preconception BMI.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%